Preoperative uterine artery embolisation before hysterectomy in women with giant uterine fibroid and HIV-associated nephropathy - Szkodziak, Filip; Woźniak, Sławomir; Światłowski, Łukasz; Maleszyk, Emilia; Szkodziak, Piotr; Pyra, Krzysztof; Berczi, Viktor; Paszkowski, Tomasz; Jargiełło, Tomasz (Menopause Review/Przegląd Menopauzalny, 2024)
Uterine fibroids are the most common pelvic benign tumours occurring in women of reproductive age. Current treatment options include surgical procedures, pharmacological therapies, and minimally invasive procedures. The most commonly applied and accepted minimally invasive procedure used in the treatment of symptomatic uterine fibroid is uterine artery embolisation (UAE). Uterine artery embolisation is a minimally invasive procedure that can be used either as an auxiliary method or the main treatment method of symptomatic uterine fibroids. We would like to present the application of pre-operative UAE before hysterectomy in anaemic women with giant uterine fibroid (21.9 × 14.9 × 10.4 cm) and HIV-associated nephropathy. Among the possible treatment options for uterine fibroids in cases like the one presented in our manuscript, hysterectomy is the treatment of choice. However, surgical treatment in a patient with severe comorbid conditions and giant uterine fibroid carries serious risk of perioperative complications. Pre-operative UAE decreases such risk by reducing blood loss during hysterectomy and shortening operation/anaesthesia time. Although the benefits of pre-operative UAE before planned myomectomy or hysterectomy in high surgical risk patients with large fibroids has yet to be confirmed in a well-designed clinical trial, this procedure seems to be a promising tool to reduce the risk of perioperative complications in such patients.